2010
DOI: 10.4049/jimmunol.1001596
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Immunotherapy Increases β Cell Regenerative Factor Reg2 in the Pancreas of Diabetic Mice

Abstract: Insulin-producing β cells can partially regenerate in adult pancreatic tissues, both in human and animal models of type 1 diabetes (T1D). Previous studies have shown that treatment with mycobacterial adjuvants such as CFA and bacillus Calmette-Guérin prevents induction and recurrence of T1D in NOD mice with partial recovery of β cell mass. In this study, we investigated factors involved in the regeneration of β cells in the pancreas of NOD mice during diabetes development and after treatment with adjuvants. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
27
1
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 57 publications
7
27
1
4
Order By: Relevance
“…mice; the increase correlated with a reduction in insulitis (Huszarik et al, 2010). On the other hand, our result of C57B/L6 mice did not support previously reported Reg2 expression in pancreatic b-cells of NOD mice, which might be caused by strain differences (Gurr et al, 2007).…”
Section: Discussioncontrasting
confidence: 78%
“…mice; the increase correlated with a reduction in insulitis (Huszarik et al, 2010). On the other hand, our result of C57B/L6 mice did not support previously reported Reg2 expression in pancreatic b-cells of NOD mice, which might be caused by strain differences (Gurr et al, 2007).…”
Section: Discussioncontrasting
confidence: 78%
“…Reg2 showed a different pattern from Reg1; it tended to increase due to damage but was significantly upregulated by the combination of damage plus IMT504, indicating that it could be one of the mechanisms by which IMT504 induces ␤-cell regeneration, as evidenced by increased ␤-cell proliferation in the short-term analysis and recuperation of ␤-cell area in the long-term analysis. Similar to our results, other authors have demonstrated that Reg2 plays a dominant role in endogenous ␤-cell regeneration following adjuvant immunotherapy in diabetic mice (24,25). Interestingly, all murine Reg genes carry one or more IL-6 response elements in their 5= flanking region (20).…”
Section: (46) Demonstrated Increasedsupporting
confidence: 80%
“…[35] podkreślają raczej możliwość samoreplikacji istnieją-cych komórek beta niż ich powstawanie z komó-rek macierzystych. Poza tym różne czynniki mogą wpływać na regenerację komórek beta poprzez wzrost ekspresji Reg l i Reg 2 (regenerating genes) w wyspach [36,37]. Levetan i wsp.…”
Section: Proliferacjaunclassified
“…2015.14.3.52. [35][36][37][38][39][40] Próby hamowania destrukcji oraz stymulacji odnowy komórek beta trzustki w cukrzycy typu l beta może być efektem proliferacji prekursorów (preexisting) komórek beta. Collombat i wsp.…”
unclassified